Motivational Factors and Constraints faced by Men and Women Self-Help Groups - V. Chinmayi; Basavaraj Beerannavar; J. Raghuraja (Journal of Agricultural Extension Management, 2015)
This study was carried out in Shivamogga district of Karnataka state to identify the motivational factors and constraints of men and women self-help groups. In all, 150 respondents covering 30 SH Gs were interviewed. The study revealed that with respect to motivational factors, men formed into self-help groups to reduce financial problems ( 54.67% ), improve social status ( 45.33%) and women groups were formed to increase future savings (7 4. 67% ), improve social status ( 64%) and obtain financial support (62.67%). The major constraints faced by the men self help groups were lack of technical guidance (42.67%), lack of training and skill development facility (38.67%), insufficient availability of loan (17.33%) while constraints faced by women self-help groups were lack of technical guidance ( 36%), inadequate availability of raw materials for Income Generating Activities (30.67%), lack of training and skill development facility (29.33%)